Konsep Pendidikan Islam Berbasis Hikmah dalam Al-Qur’an - Abdul Kadir Abu; Didin Hafidhuddin (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2020)
This research aims to reveal The Concept of Islamic Education Based on hikmah in the Quran. This research focuses on verses using the hikmah idiom. The researcher chose-themed pronunciation because it is one of several words in Qur'an found in jawâmi'ul kalim, a short sentence whose context is full of the substance of ibrah that Allah reveals to humans. This research used thematic approaches and focused on the in-kind descriptive study of library research. This research showed that hikmah's idea was very representative in shaping character development for teachers, students, and sources of material and methods of teaching. The essence of al-hikmah mixed with al-khibar (knowledge), al-miran (training), and at-tarjih (experience) components. On this basis, in the course of internalizing a range of knowledge, skills, and mental attitudes commendable to students, the model of the creation and implementation of Islamic education methods must be carried out thoroughly integrally and systematically.